Influence of the galvanized coating thickness and process parameters on heat generation and strength of steel spot welds. (March 2021) - Andrade, D.G.; Sabari, S. Sree; Leitão, C.; Rodrigues, D.M.
Abstract: The influence of galvanized coating thickness, tool diameter and rotational speed, on the thermal cycles, in spot welding of steels produced by Tool Assisted Friction Welding (TAFW), a Friction Stir Spot Welding (FSSW) related technique, is analysed. To study the influence of the galvanized coating thickness on the thermal cycles, thin steel plates commonly used in steel construction and automotive industry with galvanized coatings of varied thicknesses were welded. Numerical simulation of the welding process was conducted to understand some of the physical phenomena observed experimentally. Numerical and experimental results were compared and discussed. The influence of the above described parameters, as well as of the dwell time, on welds strength was also characterized. The results showed that steel spot welds with very good mechanical strength can be obtained in very short process cycle times. It was also determined that the welds strength was much higher than the minimum strength recommended for resistance spot welds (RSW). Graphical abstract: Image 1 Highlights: Numerical and experimental analysis of the Tool Assisted Friction Welding process. Identification of the mechanisms governing contact the conditions and heat generation. Analysis of the influence of process parameters on FSW thermo-mechanisms. Analysis of the influence of base materials surface condition on thermo-mechanisms. Analysis of process cycle times on joints strength.